Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a,Cách 1: (6/11 + 5/11 ) x 3/7 Cách 2 :(6/11 + 5/11) x 3/7
= 1 x 3/7 =6/11 x 3/7 + 5/11 x 3/7
= 3/7 = 18/77 + 15/77
= 3/7
b, Cách 1:3/5 x 7/9 - 3/5 x 2/9 Cách 2 :3/5 x 7/9 - 3/5 x 2/9
= 7/15 - 2/15 = 3/5 x (7/9 - 2/9 )
= 1/3 = 3/5 x 5/9
= 1/3
c, Cách 1:(6/7 - 4/7) : 2/5 Cách 2: ( 6/7- 4/7 ) : 2/5
= 2/7 : 2/5 = 6/7 : 2/5 - 4/7 : 2/5
= 5/7 = 15/7 - 10/7
= 5/7
d,Cách 1:8/15 : 2/11 + 7/15 : 2/11 Cách 2:8/15 : 2/11 +7/15 : 2/11
= 88/30 + 77/30 =(8/15+7/15) :2/11
= 11/2 = 1 : 2/11
= 11/2
Bài 2 cậu tự làm nhé !
\(a.60\times\left(\frac{7}{12}+\frac{4}{15}\right)\)
\(=60\times\left(\frac{35}{60}+\frac{16}{60}\right)\)
\(=60\times\frac{51}{60}\)
\(=51\)
\(b.\frac{1}{2}\times\frac{2}{3}\times\frac{3}{4}\times\frac{4}{5}\times\frac{5}{6}\times\frac{6}{7}\times\frac{7}{8}\times\frac{8}{9}\)
\(=\frac{1\times2\times3\times4\times5\times6\times7\times8}{2\times3\times4\times5\times6\times7\times8\times9}\)
\(=\frac{1}{9}\)
#) Giải :
a) \(\frac{5}{6}\)x \(\frac{6}{7}\)x \(\frac{7}{8}\): \(\frac{15}{16}\)= \(\frac{5}{8}\): \(\frac{15}{16}\)= \(\frac{5}{8}\)x \(\frac{16}{15}\)= \(\frac{80}{120}\)= \(\frac{4}{5}\)
b) \(\frac{4}{7}\)x \(\frac{7}{10}\)x \(\frac{3}{4}\) : \(\frac{9}{20}\)= \(\frac{2}{5}\)x \(\frac{3}{4}\): \(\frac{9}{20}\)= \(\frac{3}{10}\): \(\frac{9}{20}\)= \(\frac{60}{90}\)= \(\frac{2}{3}\)
#) Chúc bn học tốt :D
\(=\frac{5x6x7}{6x7x8}x\frac{16}{15}\\ =\frac{5}{8}x\frac{16}{15}\\ =\frac{2}{3}\)
b)\(=\frac{4x7x3}{7x10x4}x\frac{20}{9}\\ =\frac{3}{10}x\frac{20}{9}\\ =\frac{2}{3}\)
b)\(=\frac{4x7x3}{7x10x4}x\frac{20}{9}\\ =\frac{3}{10}x\frac{20}{9}\\ =\frac{2}{3}\)
1/2 + 4/3 = 3/6 + 8/6 = 11/6
4/5 + 3/4 : 2/3 = 4/5 + 3/4 * 3/2 = 4/5 + 9/8 = 32/40 + 45/40 = 77/40
7/2 - 4/3 * 1/6 = 7/2 - 2/9 = 63/18 - 4/18 = 59/18
4/5 * 4/7 : 2/3 = 16/35 : 2/3 = 16/35 * 3/2 = 24/35
1/4 : 5/3 + 1/6 = 1/4 * 3/5 + 1/6 = 3/20 + 1/6 = 9/60 + 10/60 = 19/60
3 - 4/5 : 1/3 = 3 - 4/5 * 3/1 = 3 - 12/5 = 15/5 - 12/5 = 3/5
5/9 * 2/7 - 3/7 = 10/63 - 3/7 = 10/63 - 27/63 = -17/63
\(\dfrac{3}{7}\times\dfrac{4}{6}\)
\(=\dfrac{3}{7}\times\dfrac{2}{3}\)
\(=\dfrac{3\times2}{7\times3}\)
\(=\dfrac{2}{7}\)
3/7 x 4/6 = 2/7